Detection of galectin-3 in tear fluid at disease states and immunohistochemical and lectin histochemical analysis in human corneal and conjunctival epithelium - Hrdlicková-Cela, E; Plzák, J; Smetana, K; Mĕlková, Z; Kaltner, H; Filipec, M; Liu, F T; Gabius, H J (The British journal of ophthalmology, 2001)
BACKGROUND/AIM: Components of the tear fluid contribute to the biochemical defence system of the eye. To reveal whether the immune mediator and lipopolysaccharide binding galectin-3 is present in tears, tear samples were collected from eyes in healthy and pathological states. Investigation of expression of galectin-3 and galectin-3 reactive glycoligands in normal human conjunctival and corneal epithelia was also initiated as a step to understand the role of galectin-3 in ocular surface pathology. METHODS: Immunoblot analysis using either a rabbit polyclonal or a mouse monoclonal antibody against galectin-3 was employed to detect galectin-3 in tear fluid. Galectin-3 expression in tissue specimens was detected by immunocytochemistry employing A1D6 mouse monoclonal antibody, and galectin-3 reactive glycoligands were visualised by lectin histochemistry using labelled galectin-3. RESULTS: Galectin-3 was found only in tears from patients with ocular surface disorders. It was expressed in normal corneal and conjunctival epithelia but not in lacrimal glands. Inflammatory leucocytes and goblet cells found in galectin-3 containing tear fluid also expressed galectin-3. Galectin-3 binding sites were detected on the surface of conjunctival and corneal epithelial cells co-localising with desmoglein. CONCLUSIONS: This study revealed expression of galectin-3 in tear fluid obtained from patients with eye diseases. The role of this endogenous lectin (produced by inflammatory as well as epithelial cells) in antimicrobial action and inflammation modulation could be expected.
Keywords: galektin 3; Conjunctiva; Electrophoresis, Polyacrylamide Gel; luminiscenční měření; Blotting, Western; lidé; pohárkové buňky; fluorescenční protilátková technika; Fluorescent Antibody Technique; konjunktiva; Eye Diseases; diferenciační antigeny; Immunoblotting; Tears; leukocyty; western blotting; Galectin 3; Goblet Cells; rohovkový epitel; Antigens, Differentiation; Leukocytes; oční nemoci; imunoblotting; Epithelium, Corneal; elektroforéza v polyakrylamidovém gelu; slzy; Luminescent Measurements; Humans